Uninsurable investment risks and capital income taxation - Césaire A. Meh; Yaz Terajima (Bank of Canada, 2009)
This paper studies the capital accumulation and welfare implications of reducing capital income taxation in a general equilibrium economy with uninsurable investment risks. It has been shown that, with uninsurable investment risks, under-accumulation of capital may result compared to the complete markets economy. We show that reducing somewhat the capital income tax rate increases the capital stock and leads to a welfare gain. The complete elimination of the capital income tax, however, is not necessarily welfare improving.
Keywords: E21; E22; E62; G32; H24; H25; 330; Economic models; Investitionsrisiko; Kapitalertragsteuer; Steuerbegünstigung; Wohlfahrtseffekt; Theorie